Medicines in medicines: Challenges and Prospects in Drug Discovery from Fungal Endophytes of Medicinal Plants in Southeast Asia: Challenges and Prospects in Drug Discovery from Fungal Endophytes of Medicinal Plants - Guerrero, Jonathan Jaime G.; General, Mheljor; Balendres, Mark Angelo; Tan, Mario; Buiza, Marielle; Huyop, Fahrul (Journal of Tropical Life Science, 2025)
Fungal endophytes engage in a balanced symbiotic continuum with their host plants, from mutualism to commensalism and parasitism. These host-endophyte interactions play a pivotal role in shaping the biosynthetic and chemical space of the host plants and their associated mycobiomes, resulting in a wealth of biologically active natural products that are attractive for drug discovery. Endophytic fungi in medicinal plants continue to attract attention, highlighting a holistic view of plant-based therapeutics that considers the plant and its endophytic partners as sources of medicinal compounds. In this review, we assembled recent Southeast Asian studies related to fungal endophytes from plants with traditional medicinal uses and their potential biomedical applications. Here, we present a comprehensive analysis of the interactions within the region, identifying prolific fungal classes that produce compounds of biomedical significance. This analysis is based on a consolidated dataset of over 1,300 interactions. We noted an association between plant-endophyte-synthesized compounds and their related chemistry. However, the majority are preliminary and lack comprehensive follow-through research. While fungal endophytes in the region produce important compounds, their applicability in drug discovery necessitates extensive long-term studies.